Developing Videos Through Project-Based Learning: Improving Aviation Cadets’ Basic Airport Civil Engineering - Fatmawati, Fatmawati; Rochmawati, Laila; Sukma, Meita Maharani; Kusumayati, Lusiana Dewi; Sukomardojo, Tekat (Formosa Journal of Multidisciplinary Research, 2024)
This study aimed to explain project-based learning (PjBL) in the context of making airside and landside learning videos for aviation cadets and measure the effectiveness of the learning videos in improving their understanding of basic airport civil engineering material. This study used ADDIE development method to develop learning videos integrated in a project-based learning process with a quantitative approach. There were 48 cadets included in this study selected using a purposive sampling technique. A total of 24 cadets joined the control class taught using conventional learning method and a total of 24 cadets participated in the experimental class taught using PjBL by developing learning videos. Data were collected using needs analysis questionnaire, rating scale for understanding basic airport civil engineering material, and validation sheet. The obtained data were analyzed using descriptive statistics and t-test to address the research questions. Results showed that the cadets were able to develop valid learning videos through ADDIE procedure and they could increase their understanding on basic airport civil engineering significantly (F = 3.533; t = .969; p = .000).